Recent Northward Expansion of a Passerine Bird Species, Brownish-Flanked Bush Warbler (Horornis fortipes) - Qianyi Zhang; Per Alström; Canwei Xia (Animals, 2023)
Northward expansions of bird distributions have been commonly observed in the Northern Hemisphere, likely as a result of climate change. The causes and ecological impacts of such range shifts have received extensive attention, but studies on the process of range shifts are still relatively scarce. The Brownish-flanked Bush Warbler (Horornis fortipes) has expanded northward from 35° N to 40° N during the past decade. In this study, we collated 77 records of the species beyond its traditional distribution during the past ten years from citizen science data. Most of the new records were from northeast of its traditional distribution, including the North China Plain, Taihang Mountains, and Taishan Mountain, and a few records from the northern margin of the Qinling Mountains and Qinghai–Tibet Plateau. We concluded that the Brownish-flanked Bush Warbler has bred in this new area in at least six sites. The newly established populations are assumed to belong to the subspecies H. f. davidianus, which can be divided into eastern and western dialect groups based on differences in songs. Song recordings from 10 males from Beijing and its adjacent areas were collected. Bayesian analysis based on the acoustic traits indicated that these males were most likely from the western dialect area, with a posterior probability of 99.975%. Combining topographical data with the habitat preference of the species, we inferred that these individuals spread northeastward from the Qinling Mountains to Taihang Mountains, and further along the Yanshan Mountains. This study is a case study of the distribution expansion of a bird species, which reflects the dynamics of a species in the early stage of its northward expansion.